REVOLUSI INDUSTRI, LEDAKAN PENDUDUK DAN MASALAH LINGKUNGAN - M Baiquni (Teknik Lingkungan Universitas Islam Indonesia, 2009)
Our civilization has dractically changed since new scientific revolution led to technological inventions and accelletared by industrial revolution. Human dominated to the nature. During industrial revolution the number of population has increased sharply and their lifestyle and consumption level has achieved certain level beyond that in the past. By the time natural resources is being exploited and environmental pollution and degradation is becoming worse. Ironically human welfare is not distributed equally, social gaps are wide and conflicts often happen, which are related to moral degradation. The end of this paper is a reflection on the human mandate to lead the world, Khalifah fil Ardh.